The Issue of Human Factor Fiction in Automated Decision-Making Under Administrative (Discourse of Law and Administration, 2024)
The fiction of a human factor is based on implementing solutions in administrative law, which require automatisation of decisions and seemingly leaving the competence in that  area to a human being or a group of people. In the text, the problem is shown through the context of the development of legal provisions in the Polish administrative law connected to the automatisation of decision making. The analysis shows that the phenomenon of the fiction of a human factor still occurs in the law, however current attempts in implementing competence to automated decisions are inconsistent and conducted according to unclear criteria regarding allowing such decisions.
Keywords: automatisation; automated decision making; communication and information system